Education: Beyond Theories and Indoctrination - Angwaomaodoko, Ejuchegahi Anthony (Journal of Education and Training, 2024)
Modern education acknowledges the inadequacy of traditional methods of teaching and learning, recognizing that mere theories and indoctrination lack depth and innovation. The paper focuses on the ways in which education can move beyond the traditional modes of approach such as indoctrination and theories to usher in new educational methods that are built around critical thinking, inquiry-based learning, and problem-solving. By moving away from such education, educators can create a learning environment within which learners are capable of effectively and critically engaging their content, constructing knowledge, and also being capable of challenging assumptions. Thorough research on Literature reviews and case studies indicated the extent to which transformative educational approaches may empower intellectual curiosity, creativity, and independent thought. This transformational approach presents some challenges. The concerted efforts to overcome these challenges require evidence-based research that is able to demonstrate the effectiveness of the alternative ways. In conclusion, the major aim of education should be to develop well rounded individuals who are not only knowledgeable but also capable of thinking innovatively.